2004
DOI: 10.1093/geronb/59.1.p35
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Disability Among Middle-Aged and Older Adults: The Role of Assimilative and Accommodative Coping

Abstract: The purpose of this study was to investigate the links among coping, disability, and mental health among adults who are confronted with age-related vision loss. Drawing on the model of assimilative and accommodative coping (e.g., Brandtstädter, 1999), hierarchical regressions were designed to examine the effects of coping and disability on mental health. Participants were 55 middle-aged and 52 older adults who had been recruited from a community-based rehabilitation agency. Findings demonstrate a critical role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 31 publications
13
132
1
2
Order By: Relevance
“…We reported earlier that physical activity goals correlate with a higher level of physical activity in old age even after adjustment for differences in health (Saajanaho et al 2014b). Previously, it has been emphasized that goal disengagement may help people adjust to age-related changes (Freund et al 2009) and so benefit psychological well-being in old age (Boerner 2004;Heyl et al 2007). The present cross-sectional results warrant future study on whether maintaining goals for physical and leisure-time activities, regardless of diminished health resources, might lead to better outcomes in terms of physical functioning.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We reported earlier that physical activity goals correlate with a higher level of physical activity in old age even after adjustment for differences in health (Saajanaho et al 2014b). Previously, it has been emphasized that goal disengagement may help people adjust to age-related changes (Freund et al 2009) and so benefit psychological well-being in old age (Boerner 2004;Heyl et al 2007). The present cross-sectional results warrant future study on whether maintaining goals for physical and leisure-time activities, regardless of diminished health resources, might lead to better outcomes in terms of physical functioning.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, age differences in older people's goal setting are, at least in part, explained by differences in life resources, most notably in health and functioning. A well-balanced whole of personal goals, as well as goal modification when needed, may have positive influences on mental well-being in old age (Boerner 2004;Dunne et al 2011;Smith and Freund 2002). This study raises the question of what will be the consequences for the physical functioning of older people, if they disengage from activity goals when faced with functional decline.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…21,90,120,130 There is less evidence regarding the impact of visual impairment on younger adults and children; however, it has been suggested that the risk of mental health problems associated with visual impairment is at least as high in those of working age as in older adults. 13,14 One recent study suggested that visual impairment occurring in middle age, rather than in later life, is more disruptive and associated with a greater risk of negative consequences for the individual. 16 A study investigating health related quality-of-life in 79 children with visual impairments, found that there was a wide range of scores on the Health Utilities Index and that the outcome was related to the comorbidities of the individuals.…”
Section: A Consequences Of Visual Impairmentmentioning
confidence: 99%
“…Average 5 home visits by rehabilitation teachers (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Average number of hours nearly 7 (range 1-21).…”
Section: Engel Et Al 2000mentioning
confidence: 99%